2018
DOI: 10.1007/s13105-018-0646-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of branched-chain amino acids on muscles under hyperammonemic conditions

Abstract: The aim was to determine the effects of enhanced availability of branched-chain amino acids (BCAAs; leucine, isoleucine, and valine) on ammonia detoxification to glutamine (GLN) and protein metabolism in two types of skeletal muscle under hyperammonemic conditions. Isolated soleus (SOL, slow-twitch) and extensor digitorum longus (EDL, fast-twitch) muscles from the left leg of white rats were incubated in a medium with 1 mM ammonia (NH3 group), BCAAs at four times the concentration of the controls (BCAA group) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
8
0
6
Order By: Relevance
“…The alterations indicate enhanced synthesis of GLN from GLU and the shift of GLU metabolism from its use as a donor of nitrogen to pyruvate for synthesis of ALA to GLN synthesis. The BCAAs decrease due to their use as donors of nitrogen to α‐KG for synthesis of GLU, which is a direct substrate for ammonia detoxification to GLN …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The alterations indicate enhanced synthesis of GLN from GLU and the shift of GLU metabolism from its use as a donor of nitrogen to pyruvate for synthesis of ALA to GLN synthesis. The BCAAs decrease due to their use as donors of nitrogen to α‐KG for synthesis of GLU, which is a direct substrate for ammonia detoxification to GLN …”
Section: Discussionsupporting
confidence: 91%
“…The BCAAs decrease due to their use as donors of nitrogen to α-KG for synthesis of GLU, which is a direct substrate for ammonia detoxification to GLN. 12,13 Unfortunately, the number of studies which refer to amino acid changes in the muscles due to cirrhosis is limited and most of the data are older. A marked decrease in the BCAA in muscles in patients with cirrhosis was reported by Iob et al 32 Plauth et al 33 reported decreased levels of VAL and ILE, and unaltered concentration of LEU, in quadriceps femoris muscle.…”
Section: Alterations In Amino Acid Concentrations In Muscles Relatementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that high levels of ammonia increase the catabolism of branched-chain amino acids (BCAAs; leucine, isoleucine, and valine) [ 4 , 5 , 6 , 7 ], resulting in decreased BCAA levels in liver cirrhosis [ 8 , 9 , 10 , 11 ] and UCDs [ 12 , 13 ]. Due to their positive influence on protein balance and the detrimental role of decreased BCAA levels in the pathogenesis of hepatic encephalopathy, BCAAs have been recommended for patients with liver cirrhosis for almost 50 years [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…BCAAs can significantly affect the stimulation of the mammalian target of the rapamycin (mTOR) kinase pathway and thus stimulate the synthesis of muscle proteins, as well as have anti-catabolic activity, related to inhibition of muscle protein proteolysis [1,2,3]. The above mechanisms may explain the observed effect of BCAA supply on the exercise-induced muscle damage, pain, fatigue or injury reduction, and the acceleration of fat-free mass or strength recovery [1,2,4,5].…”
Section: Introductionmentioning
confidence: 99%